2012
DOI: 10.1373/clinchem.2011.172940
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Plaque Instability in the Early Diagnosis and Risk Stratification of Acute Myocardial Infarction

Abstract: BACKGROUND:Plaque erosion and plaque rupture occur early in the pathophysiology of acute myocardial infarction (AMI). We hypothesized that markers of plaque instability might be useful in the early diagnosis and risk stratification of AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 42 publications
2
32
0
1
Order By: Relevance
“…Similar results were reported by other authors (11)(12)(13)(14)(15). Researches showed that there is a significant correlation between the CRP with an increased risk of cardiovascular death.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were reported by other authors (11)(12)(13)(14)(15). Researches showed that there is a significant correlation between the CRP with an increased risk of cardiovascular death.…”
Section: Discussionsupporting
confidence: 91%
“…[14] was divided into two cohorts because they provided separated data for patients with ST-segment elevated myocardial infarction and non-ST-segment elevated ACS, respectively. Finally, 14 prospective studies (15 independent cohorts) concerning 12 830 participants and 1813 cases were included in our meta-analysis [917, 1923]. Of the 15 cohorts, there were 7 endpoints of all-cause mortality [11, 12, 1417, 23], 7 combinations of all-cause mortality and non-fatal MI [1216, 20, 22], and 4 combinations of cardiac death, MI or revascularization [9, 10, 19, 21].…”
Section: Resultsmentioning
confidence: 99%
“…Among ACS patients of the FAST-MI, authors found that low fetuin-A and high hs-CRP concentrations were associated with cardiovascular death, even after adjustment for GRACE risk score [132] . In another study by Schaub et al [133] in 398 consecutive patients presenting with acute chest pain novel biomarkers like myeloperoxidase, MRP-8/14 and hs-CRP, provided incremental value in the risk stratification of these patients.…”
Section: Modulation Of Inflammationmentioning
confidence: 99%